2009
DOI: 10.1073/pnas.0900251106
|View full text |Cite
|
Sign up to set email alerts
|

Paleocene emergence of elephant relatives and the rapid radiation of African ungulates

Abstract: Elephants are the only living representatives of the Proboscidea, a formerly diverse mammalian order whose history began with the 55-million years (mys) old Phosphatherium. Reported here is the discovery from the early late Paleocene of Morocco, ca. 60 mys, of the oldest and most primitive elephant relative, Eritherium azzouzorum n.g., n.sp., which is one of the earliest known representatives of modern placental orders. This well supported stem proboscidean is extraordinarily primitive and condylarth-like. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
99
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(109 citation statements)
references
References 26 publications
10
99
0
Order By: Relevance
“…Upper Paleocene and Lower Eocene deposits have yielded a huge amount of marine vertebrates (e.g., Arambourg, 1952;Noubhani and Cappetta, 1997;Jalil et al, 2006;Jouve et al, 2008), including seabirds (Bourdon et al, 2008a(Bourdon et al, , 2008b; this study). The strong condensation of the phosphate series in the northeastern margin of the basin indicates the proximity of the shore and is in accordance with the presence of mammals (Gheerbrant et al, 2006;Gheerbrant, 2009;Solé et al, 2009).…”
Section: Paleoecology and Paleoenvironment Of Dasornissupporting
confidence: 71%
See 1 more Smart Citation
“…Upper Paleocene and Lower Eocene deposits have yielded a huge amount of marine vertebrates (e.g., Arambourg, 1952;Noubhani and Cappetta, 1997;Jalil et al, 2006;Jouve et al, 2008), including seabirds (Bourdon et al, 2008a(Bourdon et al, , 2008b; this study). The strong condensation of the phosphate series in the northeastern margin of the basin indicates the proximity of the shore and is in accordance with the presence of mammals (Gheerbrant et al, 2006;Gheerbrant, 2009;Solé et al, 2009).…”
Section: Paleoecology and Paleoenvironment Of Dasornissupporting
confidence: 71%
“…Some studies suggest a warm, humid climate and tropical forests near the shore of the Moroccan phosphate sea (Boureau, 1951;Herbig and Gregor, 1990). This is compatible with the discovery of various folivorous mammals such as proboscideans and hyracoids (Gheerbrant et al, 2003;Gheerbrant, 2009). Moreover, a palynological study of the Moroccan phosphates has shown the uniformity of Moroccan and European floras in the Paleocene and Lower Eocene (Ollivier-Pierre, 1982).…”
Section: Paleoecology and Paleoenvironment Of Dasornismentioning
confidence: 77%
“…The last possibility is perhaps the most likely, given the dearth of obvious apomorphies characterizing the four placental superorders [1]. However, our analyses also place numerous subsequent divergences within Placentalia well before the K-Pg boundary (see the electronic supplementary material, §7); several of these involve clades with distinctive apomorphies, Glires [2,6,50] and Paenungulata [2,51,52]. We thus prefer an alternative explanation, namely that the models employed here are overestimating divergence times within Placentalia, and presumably also within Eutheria as a whole.…”
Section: Discussionmentioning
confidence: 79%
“…The prominent conules are larger than those in even the most primitive perissodactyls. This may be a uniquely derived trait of cambaytheres and anthracobunids; and it contrasts with basal proboscideans, which lack molar conules 21 . The premolars exhibit little molarization compared with those of early perissodactyls.…”
Section: Fossilmentioning
confidence: 99%
“…It is otherwise very similar to Cambaytherium and it, too, was placed in Perissodactyla. However, other taxa that can now be shown to be cambaytheres (Nakusia shahrigensis 20 , Indobune vastanensis 17 ) were originally allocated to Anthracobunidae, a family most recently interpreted as either stem Tethytheria 21 or stem Proboscidea 11,20,[22][23][24] . Anthracobunidae were previously considered either artiodactyls or perissodactyls 25 .…”
mentioning
confidence: 99%